Futebol, telejornalismo e público: a criação de vínculos - Arrebola, Talita Lima Chechin Camacho (2022)
Football is a sport that mobilizes, loves and influences the behavior of the population. By examining the effects produced by the modality on the television medium, this research sought to identify the links between the news and football, focusing on the coverage of Copa América 2019 and 2021 by Jornal Nacional and SBT Brasil, and with emphasis on the respective rhetorical inflections before and during the COVID19 pandemic. For this, the research corpus comprises the editions of Jornal Nacional from June 14 to July 08, 2019, Copa América 2019, in addition to the editions of the SBT Brasil and Jornal Nacional news from June 10 and July 12, 2021, period that comprises the coverage of Copa América 2020, held in 2021. The methodology of this work was based on content analysis, which aims to investigate the concepts around an object. The investigation of the collected data adopts the phases defined by Bardin (2002): pre-analysis; exploration of the material and treatment of the results. By exploring the stories of life, overcoming and the championship; TV news adds concepts of identification and empathy, strengthening ties and ties with the television product. The overcomings, falls, defeats and victories are counted through the editorial criteria of the broadcasters, the narrative strategies adopted by the reporters, the excerpts of the selected speeches as deserving of attention and the interpretation of certain events evaluated as relevant by the television news. In this sense, those involved are just passive characters, driven by the interests of the media, used to propagate the dominant ideology defended by the broadcaster. This process of creating bonds and ties highlights the mishaps of a championship, and places the main characters, the broadcaster and the newscast fulfilling only the marketing task, in an attempt to gain audience and generate identification through an illusory and homogeneous representation of these athletes. On the other hand, this false protagonism covers up countless situations, conveying the idea that it values and represents all football players, without taking into account the diversity and plurality of their life stories